Stucture and Diversity of Phytoplantkton’s Communities in a Ramsar Wetland (Sebkhet Bazer, Setif, Eastern Of Algeria) - Djerboua, Sabrina; Guendouz, Ali; Bachir, Abdelkrim Si; Benalia, Frih (International Journal of Bio-resource and Stress Management, 2022)
An inventory was made during the period from March 2014 to March 2016 in a Ramsar wetland, it’s the Salt Lake (Sebkhet) of Bazer, Setif region, Algeria, to study inventories of phytoplanktons and to understand the structure and the distribution of micro-algae groups according to season or function of the biotic and also physicochemical parameters of the environment. Water samples are collected bi-monthly and preserved by a special technique to conserve microelements and to better identify phytoplankton. 33 genera were identified using an optical microscope, these genera belong to 13 orders, 18 families and 6 classes: Zygophylaceae, Chlorophyceae, Diatomophyceae, Cyanophyceae, Euglenophyceae and Dinophyceae, where, the Diatomophyceae class is the most important with 12 species or 37.50%, 5 families or 27.77% and 3 orders or 23.08%.What’s more, 21, 21% of species are considered toxic, represented by 7 genera; in which 3 genera belonging to the Dinophyceae while 4 genera belonging to the Cyanophyceae. In addition, the statistical analyzes of these groups such as AFC, and PCA which were carried out using R software, confirms that the phytoplankton populations and distribution are linked to abiotic conditions, and vary with the seasons and depend both on the physicochemical factors of the environment such as the pH and temperature. These phytoplankton groups are bio-indicators of pollution, of which we noted that despite the importance of this area but it is polluted and required long-term protection.